Adjuvant bisphosphonates or RANK-ligand inhibitors for patients with breast cancer and bone metastases: A systematic review and network meta-analysis. (May 2019) - Tesfamariam, Y.; Jakob, T.; Wöckel, A.; Adams, A.; Weigl, A.; Monsef, I.; Kuhr, K.; Skoetz, N.
Highlights: Ranking of treatments compared to placebo for SREs: 1st Denosumab 2nd Zoledronic acid 3rd Pamidronate. Studies lacked sufficient information on pain, overall survival and quality of life. Network meta-analysis was not possible for patient relevant outcomes. Abstract: Bone-modifying agents like bisphosphonates and receptor activator of nuclear factor kappaβ ligand (RANK-L) inhibitors are used as supportive treatments in breast cancer patients with bone metastases to prevent skeletal-related events (SREs). Due to missing head-to-head comparisons, a network meta-analysis was performed to provide a hierarchy of these therapeutic options. Through a systematic literature search, 21 randomized controlled trials (RCTs) that fulfilled the inclusion criteria were identified. To prevent SREs, the ranking through P -scores showed denosumab (RR: 0.62; 95%CI: 0.50-0.76), zoledronic acid (RR: 0.72; 95%CI: 0.61-0.84) and pamidronate (RR: 0.76; 95%CI: 0.67-0.85) to be significantly superior to placebo. Due to insufficient or heterogeneous data, overall survival, quality of life, pain response and adverse events were not able to be analyzed within the network. Although data were sparse on adverse events, the risk of significant adverse events appeared low. The results of this review can therefore be used to formulate clinical studies more precisely in order to standardise and focus on patient-relevant outcomes.